Dielectric Properties of Ionic Liquids - Paluch, Marian; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book discusses the mechanisms of electric conductivity in various ionic liquid systems (protic, aprotic as well as polymerized ionic liquids). It hence covers the electric properties of ionic liquids and their macromolecular counterpanes, some of the most promising materials for the development of safe electrolytes in modern electrochemical energy devices such as batteries, super-capacitors, fuel cells and dye-sensitized solar cells. Chapter contributions by the experts in the field discuss important findings obtained using broadband dielectric spectroscopy (BDS) and other complementary techniques. The book is an excellent introduction for readers who are new to the field of dielectric properties of ionic conductors, and a helpful guide for every scientist who wants to investigate the interplay between molecular structure and dynamics in ionic conductors by means of dielectric spectroscopy.
Introduction to Ionic Liquids -- Rotational and translational diffusion in ionic liquids -- Charge transport and glassy dynamics in ionic liquids confined to nanoporous systems -- Electrochemical double layers in ionic liquids investigated by Broadband Dielectric Spectroscopy and other complementary experimental techniques -- Electrical properties of the interface between metals and Ionic Liquids -- Dielectric properties of protic ionic liquids -- Polymerized ionic liquids.
Keywords: Electrochemistry; Optical materials; Soft condensed matter; Polymers; Materials -- Analysis; Nanotechnology; Electrochemistry; Optical Materials; Soft and Granular Matter; Polymers; Characterization and Analytical Technique; Nanotechnology